Phenotypic characterization of a female patient with retinitis pigmentosa caused by a homozygous X-linked RPGRORF15 mutation - Marlene Saßmannshausen; Elisa A. Mahler; Sandrine H. Künzel; Constanze L. Kochs; Frank G. Holz; David Rosenkranz; Hanno J. Bolz; Philipp Herrmann (American Journal of Ophthalmology Case Reports)
Purpose: To describe a detailed phenotypic expression of a homozygous female with retinitis pigmentosa (RP) within a consanguineous family revealing an extremely rare genetic constellation with possible implications for future emerging therapies in addressing inherited retinal dystrophies. Observations: Multimodal retinal imaging including wide field fundus photography, fundus autofluoresence (FAF), high-resolution spectral domain optical coherence tomography (SD-OCT) imaging, functional testing comprising visual fields and electroretinogram as well as genetic testing were performed in two consanguine cases of RP.A 44-year-old female patient was referred for evaluation and counseling for potential treatment options presenting with night blindness and visual field defects since early childhood. Extended ophthalmologic examination including multimodal retinal imaging and functional testing showed a clinical presentation of a RP phenotype. The accompanying 50-year-old paternal uncle reported similar visual symptoms and was diagnosed with RP during adolescence. In multimodal retinal imaging, both patients presented a similar phenotype and comparable disease severity with a global photoreceptor loss and decreased FAF signal. In the uncle, there was evidence for central residuals of the photoreceptor band on SD-OCT imaging and a patchy FAF pattern. Genetic testing revealed a rare constellation of a homozygous RP GTPase Regulator protein (RPGRORF15) mutation in the female patient. Conclusions and importance: This detailed phenotype-genotype correlation presents a novel clinical presentation of a rare homozygous RPGRORF15 mutation in a female patient that exhibits severe retinal degeneration similar to affected males and therefore, considering they don't have a wildtype allele, may be suitable for inclusion in upcoming therapeutic treatment trials.